Separation of whey proteins for chromatography liquid - Giraldo, Abraham (2010)
This paper describes and compares three chromatographic methods for the analysis and quantification of most abundant proteins in cheese whey, α-lactalbumin and β-lactoglobulin. The methods were: Reverse-phase high performance liquid chromatography, anion Exchange chromatography and size-exclusion chromatography. The reverse- phase liquid chromatography led to a better separation of whey proteins than size-exclusion chromatography and anion exchange chromatography, this method offered an excellent separation for whey proteins and presented a short time of analysis (33 min).